Rosin modified acrylic emulsion for liquid barrier coating compositions
Styrene-free multistage polymers, particularly rosin-modified acrylic emulsions, address the need for coatings with good liquid barrier performance and block resistance in food packaging, utilizing biorenewable sources to enhance stability and meet food contact requirements.
Patent Information
- Application Number
- JP2024536009
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-16
- Filing Date
- 2022-12-15
- Publication Date
- 2025-01-22
AI Technical Summary
The printing and packaging market requires coatings that meet food contact requirements and provide good liquid barrier performance and block resistance without using styrene, due to health concerns associated with styrene use.
The development of styrene-free multistage polymers, specifically rosin-modified acrylic emulsions, which are manufactured through a process involving a resin dispersion, polymer seed, and radical emulsion polymerization, utilizing biorenewable sources like fumarate esters, to create a polymer emulsion with a bimodal or multimodal particle size distribution.
The resulting coatings exhibit improved liquid barrier performance, block resistance, and are suitable for food contact applications, offering enhanced stability and performance compared to traditional coatings.
Smart Images

Figure 2025501515000001 
Figure 2025501515000002 
Figure 2025501515000003
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This disclosure relates generally to styrene-free multi-stage polymers and coating compositions containing the multi-stage polymers for use in a variety of applications. [Background technology]
[0002] The printing and packaging market requires coating dispersions that meet food contact requirements and have good liquid barrier performance and block resistance for functional packaging applications. Many existing coatings contain styrene. However, the use of styrene for such applications is becoming less desirable due to possible health concerns. Summary of the Invention [Problem to be solved by the invention]
[0003] Improvements in currently used coatings are needed. [Means for solving the problem]
[0004] The present disclosure provides a method for producing a polymer emulsion, comprising: i) providing a resin dispersion comprising at least one resin in an aqueous solution; ii) adding a polymerization mixture comprising at least one polymer seed and at least one copolymerizable monomer to the resin dispersion; and iii) preparing a polymer emulsion in water by radical emulsion polymerization of the polymerization mixture, the resin dispersion and the polymer seeds.
[0005] The resin may include rosin derived from bio-renewable sources such as fumaric acid esters.
[0006] The present disclosure further provides water-based compositions and coatings of the polymer emulsions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The claimed invention is not limited with respect to the embodiments described in this application. As will be apparent to one skilled in the art, modifications and variations can be made without departing from the spirit and scope thereof. In addition to those enumerated herein, functionally equivalent methods, formulations, and devices within the scope of the present disclosure will be apparent to one skilled in the art from the foregoing description. Such modifications and variations are intended to be included within the scope of the appended claims. The present disclosure is to be limited only by the terms of the appended claims, along with the full scope of equivalents to which such claims are entitled. It is to be understood that the present disclosure is not limited to methods, reagents, compounds, or compositions, which may, of course, vary. It is also to be understood that the terminology used herein is for the purpose of describing the embodiments only, and is not intended to be limiting.
[0008] Furthermore, terms such as "(a)", "(b)", "(c)", "(d)" and the like in the specification and claims are used to distinguish between similar elements and are not necessarily intended to describe a sequential or chronological order. It is understood that such terms used are interchangeable under appropriate circumstances and that embodiments of the subject matter described herein can be performed in other orders than those described or illustrated herein. When terms such as "(A)", "(B)", and "(C)", or "(a)", "(b)", "(c)", "(d)", "(i)", "(ii)", and the like refer to steps of a method or use or assay, there is no consistency of time or time interval between the steps. That is, unless otherwise indicated herein above or below in this application, the steps may be performed simultaneously or there may be a time interval of seconds, minutes, hours, days, weeks, months, or even years between such steps.
[0009] For purposes of the claimed invention, when features or aspects of the disclosure are described in terms of a Markush group, one of skill in the art will recognize that the disclosure is also thereby described in terms of any individual element or subgroup of elements of the Markush group.
[0010] For purposes of the claimed invention, all ranges disclosed herein also encompass any and all possible subranges and combinations of subranges. Ranges defined throughout the specification include endpoint values. That is, a range of 1 to 10 means that both 1 and 10 are included in the range. For the avoidance of doubt, applicants shall have equivalent rights pursuant to applicable law. Any recited range can be readily recognized as fully descriptive and allowing for division of the same range into at least equal halves, thirds, quarters, fifths, tenths, etc. As a non-limiting example, each range discussed herein can be readily divided into a lower third, middle third, upper third, etc. Also, as will be understood by those of skill in the art, all language such as "up to," "at least," "greater than," "less than," etc., refers to a range that is inclusive of the recited numbers and that can be subsequently divided into subranges as discussed above. Finally, as will be understood by those of skill in the art, a range includes individual members. Thus, for example, a group having 1 to 3 cells refers to a group having 1, 2, or 3 cells. Similarly, a group having 1-5 cells refers to groups having 1, 2, 3, 4 or 5 cells, etc.
[0011] Use of the terms "a," "an," "the," and similar referents in the context of describing the materials and methods discussed herein (particularly in the context of the claims which follow) should be construed to encompass both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context.
[0012] The term "about" used throughout this specification is used to describe and explain small variations. For example, the term "about" refers to ±5% or less, such as ±2% or less, ±1% or less, ±0.5% or less, ±0.2% or less, ±0.1% or less, or ±0.05% or less. All numerical values in this specification are modified by the term "about", whether or not explicitly stated. Values modified by the term "about" of course include the specific value. For example, "about 5.0" must include 5.0.
[0013] In the following passages, different aspects of the subject matter are defined in more detail. Each aspect so defined can be combined with any one or more of the other aspects, unless expressly indicated otherwise. Any feature indicated as being preferred or advantageous can be combined with any one or more of the other features indicated as being preferred or advantageous.
[0014] References throughout this specification to "one embodiment" or "an embodiment" mean that the features, structures, or characteristics described with respect to that embodiment are included in at least one embodiment of the claimed invention. Thus, the appearance of the phrases "in one embodiment" or "in an embodiment" in various places throughout this specification may refer to, but not necessarily all refer to, the same embodiment. Furthermore, features, structures, or characteristics may be combined in any suitable manner in one or more embodiments, as would be apparent to one of ordinary skill in the art from this disclosure. Furthermore, as would be understood by one of ordinary skill in the art, some embodiments described herein include some features that are not included in other embodiments, but combinations of features of various embodiments are within the scope of the subject matter and are meant to form different embodiments. For example, in the appended claims, any of the claimed embodiments may be used in any combination.
[0015] Although the process disclosed herein has been described with reference to embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the claimed invention. It will be apparent to those skilled in the art that various modifications and variations can be made to the method and apparatus of the claimed invention without departing from the spirit and scope of the claimed invention. Therefore, the claimed invention is intended to include modifications and variations that are within the scope of the appended claims and their equivalents, and the above embodiments are presented for purposes of illustration and not limitation. All patents and publications cited herein are incorporated by reference for the specific teachings described, unless other incorporated statements are specifically provided.
[0016] All methods described herein can be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or exemplary language (e.g., "such as") provided herein is intended merely to better describe the materials and methods and is not intended to be limiting in scope unless specifically claimed.
[0017] For purposes of the present claimed invention, the term "polymer" refers to a single polymer or a mixture of polymers that result from a formation reaction from monomers to give a macromolecule.
[0018] For purposes of the present claimed invention, "polymer emulsion" refers to an emulsion or colloidal dispersion that includes water-soluble and / or water-dispersible polymers.
[0019] For purposes of the present claimed invention, "resin dispersion" refers to a resin dispersed in water.
[0020] For purposes of the present claimed invention, "polymer seed" refers to a polymer that acts as a seed in a polymerization.
[0021] For purposes of the present claimed invention, a surfactant is defined as a surface active compound that reduces the surface tension of a liquid, the interfacial tension between two liquids, or the interfacial tension between a liquid and a solid. The terms surfactant and emulsifier are used interchangeably herein.
[0022] For purposes of the present claimed invention, "water soluble" means that the associated component or ingredients of the composition can be dissolved in the aqueous phase at a molecular level.
[0023] For purposes of the present claimed invention, "water-dispersible" means that the associated component or components of the composition may be dispersed in an aqueous phase and form a stable emulsion or suspension.
[0024] For purposes of the present claimed invention, a binder or solid binder is a non-volatile component of the polymer emulsion of the present claimed invention, exclusive of pigments and fillers.
[0025] For purposes of the claimed invention, the term "support resin" refers to a low molecular weight copolymer (weight average molecular weight of about 1500 g / mol to 35,000 g / mol) containing styrenic, acrylic and / or acidic monomers that can be dispersed in water upon neutralization of the acidic component.
[0026] For purposes of the claimed invention, the terms "aqueous" or "water-borne" as used herein refer to a significant proportion of water as the primary dispersion medium other than organic solvents.
[0027] The use of (meth) in a monomer or repeat unit indicates any methyl group. For purposes of the present claimed invention, the term "copolymer" is meant to include block or random copolymers, where the copolymer is obtained by radical polymerization.
[0028] For purposes of the present claimed invention, the term "bimodal particle size distribution" as used herein refers to two distinct groups of particle size distributions. For purposes of the present claimed invention, the term "multimodal particle size distribution" as used herein refers to more than two distinct groups of particle size distributions.
[0029] For purposes of the present claimed invention, the term "surfactant-free" is intended to mean that the polymerization was carried out without the use of a surfactant, and that no surfactant was added to the composition at any time prior to or during the formation of the emulsion.
[0030] As used herein, the term "(meth)acrylate monomer" includes acrylate, methacrylate, diacrylate, and dimethacrylate monomers.
[0031] As used herein, the term "theoretical glass transition temperature" or "theoretical T g The term "estimated T of a polymer or copolymer calculated using the Fox equation g The Fox formula may be used to estimate the glass transition temperature of a polymer or copolymer, for example, as described in LH Sperling, "Introduction to Physical Polymer Science", 2nd Edition, John Wiley & Sons, New York, p. 357 (1992) and TGFox, Bull. Am. Phys. Soc, 1, 123 (1956), both of which are incorporated herein by reference. For example, the theoretical glass transition temperature of a copolymer derived from monomers a, b, ..., and i can be calculated according to the following formula: 1Tg=w a Tg a +w b Tg b +…+w i Tg i During the ceremony, w a is the weight fraction of monomer a in the copolymer, and T gais the glass transition temperature of the homopolymer of monomer a, and w b is the weight fraction of monomer b in the copolymer, and T gb is the glass transition temperature of the homopolymer of monomer b, and w i is the weight fraction of monomer i in the copolymer, and T gi is the glass transition temperature of the homopolymer of monomer i, and T g is the theoretical glass transition temperature of a copolymer derived from monomers a, b, ..., and i.
[0032] The number average molecular weight (Mn) is the statistical average molecular weight of all the polymer chains in a polymer and is defined by: Mn = (ΣNiMi) / ΣNi where Mi is the molecular weight of a chain and Ni is the number of chains at that molecular weight.
[0033] The weight average molecular weight (Mw) is defined as follows: Mw = (ΣNiMi 2 ) / ΣNi
[0034] Compared to Mn, Mw takes into account the molecular weight of the chain in determining its contribution to the molecular weight average: the larger the chain, the more it contributes to Mw.
[0035] The higher average molecular weight (Mz) can be defined by the following formula: Mz = (ΣNiMi 3 ) / ΣNi
[0036] Dispersity index or polydispersity index (PDI) is a measure of the distribution of molecular weights in a given polymer sample. Calculate the PDI of a polymer: PDI=Mw / Mn The weight average molecular weight and the statistical average molecular weight are defined above.
[0037] The term "coating" as used herein refers to any surface treatment applied to paper. The term "barrier properties" as used herein refers to increased resistance of paper to various materials such as air, oil, grease, and higher surface strength. The term "block resistance" as disclosed herein refers to the ability of the coating not to stick to itself when applied to two surfaces upon contact or when pressure is applied. The term "oil and / or grease resistance" as disclosed herein refers to the ability of the substrate on which the coating is applied to resist the formation of surface spots or stains, or the penetration of oil / grease through the substrate.
[0038] For purposes of this disclosure, a paper or paperboard substrate or paper product as used herein can be any article of manufacture, at least a portion of which includes paper coated according to the claimed invention. The claimed invention encompasses paper products made in either single or multi-ply, such as paper laminates, plastic laminates. The terms "repulpable" or "repulpability", as used interchangeably herein, are the ability of a coated paper or paperboard substrate to undergo rewetting and fiberization operations for subsequent paper sheet formation. The terms "recycled" or "recyclability", as used interchangeably herein, are the ability of post-consumer treated paper and paperboard to be processed into new paper and paperboard.
[0039] As used herein, the term "paper-based substrate" or "paperboard substrate" refers to any type of cellulosic fiber-based product that can be folded manually or mechanically.
[0040] The present disclosure provides a method for producing a polymer emulsion comprising a multi-layer particle. The multi-layer particle may comprise a hydrophobic component and a bio-renewable component. Specifically, the multi-layer particle may comprise a hydrophobic core having functional groups arranged on the surface.
[0041] Multilayer particles may be derived from acrylate monomers and supporting resins. For example, multilayer particles can range from core-shell particles to so-called "acorn" particles, with the second layer surrounding a significant portion of the first layer, either continuously, semi-continuously or discontinuously (e.g., the second layer forms 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or less, 35% or less, 40% or less, 45% or less, or 50% or less of the particle surface). In some embodiments, the first layer and the second layer form first and second domains within the multilayer particle, with the second layer surrounding at least a portion of the first layer.
[0042] The biorenewable component of the multi-layered particles, as a percentage of the total particle mass, can be about 20% by weight or more, about 25% by weight or more, about 30% by weight or more, about 35% by weight or more, about 40% by weight or less, about 45% by weight or less, about 50% by weight or less, 55% by weight or less, 60% by weight or less, or any value encompassed by these endpoints.
[0043] The multi-layer particles can be synthesized by combining 1) a first feed of monomers ("Feed 1"), 2) a second feed of monomers ("Feed 2"), 3) a bio-renewable component, 4) a redox initiator, 4) a catalyst, and 5) a surfactant.
[0044] The present disclosure provides a method for preparing a polymer emulsion, comprising providing a resin dispersion having at least one resin in water, and adding at least one polymer seed and a polymerization mixture to the resin dispersion. The polymerization mixture has at least one copolymerizable monomer. The method comprises preparing the polymer emulsion in water by radical emulsion polymerization of the polymerization mixture, the resin dispersion and the polymer seed.
[0045] One aspect of the claimed invention is a method for preparing a polymer emulsion, comprising the steps of: i) providing a resin dispersion comprising at least one resin in an aqueous solution; ii) adding a polymerization mixture comprising at least one polymer seed and at least one copolymerizable monomer to the resin dispersion; iii) preparing a polymer emulsion in water by radical emulsion polymerization of the polymerization mixture, the resin dispersion and the polymer seeds.
[0046] An initiator may also be present in the reaction mixture. An initiator may be used to start the polymerization process. A catalyst may also be present in the reaction mixture.
[0047] The resin may be a support resin. The resin may be derived in whole or in part from bio-renewable sources. Suitable sources may include, for example, plants, trees, and by-products of the wood pulping process.
[0048] The bio-renewable resin may include a rosin ester. Suitable rosin esters may include, for example, fumaric acid esters.
[0049] The rosin ester can have an acid number of about 125 mgKOH / g or more, 150 mgKOH / g or more, about 155 mgKOH / g or more, about 160 mgKOH / g or more, about 165 mgKOH / g or more, about 170 mgKOH / g or more, about 175 mgKOH / g or less, about 180 mgKOH / g or less, about 185 mgKOH / g or less, about 190 mgKOH / g or less, about 195 mgKOH / g or less, about 200 mgKOH / g or less, or any value encompassed by these endpoints.
[0050] The number average molecular weight (Mn) of the rosin ester can be about 600 g / mol or more, about 620 g / mol or more, about 640 g / mol or more, about 660 g / mol or more, about 680 g / mol or more, about 700 g / mol or less, about 720 g / mol or less, about 740 g / mol or less, about 760 g / mol or less, about 780 g / mol or less, about 800 g / mol or less, or any value encompassed by these endpoints.
[0051] The weight average molecular weight (Mw) of the rosin ester can be about 1500 g / mol or more, about 2000 g / mol or more, about 2500 g / mol or more, about 3000 g / mol or more, about 3500 g / mol or more, about 4000 g / mol or more, about 4500 g / mol or less, about 5000 g / mol or less, about 5500 g / mol or less, about 6000 g / mol or less, about 6500 g / mol or less, about 7000 g / mol or less, about 10,000 g / mol or less, about 15,000 g / mol or less, or any value encompassed by these endpoints.
[0052] When preparing the polymer, the rosin ester can be dispersed in an aqueous solution. Suitable aqueous solutions can include, for example, aqueous ammonia. The concentration of the rosin ester in aqueous ammonia can be about 15% or more, about 20% or more, about 25% or more, about 30% or less, about 35% or less, about 40% or less, as determined by either oven (150°C, 30 min) or microwave solids analyzer.
[0053] Surfactant can then be added to the dispersion of rosin ester in the aqueous phase. Suitable surfactants can include, for example, Disponil AFX 1080 or Calfax DB45. Surfactant can be present in the reaction mixture in an amount of about 0.1% by weight or more, about 0.2% by weight or more, about 0.3% by weight or more, about 0.4% by weight or more, about 0.5% by weight or more, about 0.6% by weight or less, about 0.7% by weight or less, about 0.8% by weight or less, about 0.9% by weight or less, about 1% by weight or less, or any value encompassed by these endpoints.
[0054] The emulsion can then be initiated by adding a redox initiator. Suitable redox initiators can include, for example, isoascorbic acid (IAA), t-butyl hydroperoxide (TBHP), sodium erythroate, sodium metabisulfate, or combinations thereof.
[0055] The initiator can be provided to the reaction mixture for a period of about 60 minutes or more, about 70 minutes or more, about 80 minutes or more, about 90 minutes or less, about 100 minutes or less, about 110 minutes or less, about 120 minutes or less, or any value encompassed by these endpoints.
[0056] The initiator may be provided to the reaction mixture at a temperature of about 60° C. or greater, about 65° C. or greater, about 70° C. or less, about 75° C. or less, about 80° C. or less, or any value encompassed by these endpoints.
[0057] A catalyst may be added. Suitable catalysts may include, for example, copper(II) sulfate (CuSO4) and iron(II) sulfate.
[0058] The emulsion polymerization monomers may be added as two separate feeds: Feed 1 and Feed 2. Feed 1 may include the core of the multi-layered particle. Feed 1 may include a hydrophobic acrylic copolymer. Feed 1 may be added at a theoretical T of Feed 2. g The first theory T may be lower than g may have the following structure:
[0059] Feed 2 may include a hydrophobic acrylic copolymer. Feed 2 may be 0.1 to 0.2 times the theoretical T g The second theory T may be higher than g may have the following structure:
[0060] In some embodiments, the first theoretical Tg, as measured by DSC, can be about -30°C or higher, about -25°C or higher, about -24°C or higher, about -23°C or higher, about -22°C or higher, about -21°C or higher, about -20°C or higher, about -19°C or lower, about -18°C or lower, about -17°C or lower, about -16°C or lower, about -15°C or lower, about -10°C or lower, or any value encompassed by these endpoints, as measured by ASTM D3418-15. g can be, inter alia, from about -25°C to about -15°C, from about -18°C to about -10°C, from about -22°C to about -15°C.
[0061] The second copolymer has a T of about 10° C. or more, about 15° C. or more, about 20° C. or more, about 25° C. or more, about 30° C. or less, about 35° C. or less, about 40° C. or less, about 45° C. or less, about 50° C. or less, as measured using DSC. g , or any value encompassed by these endpoints, such as 20°C to 40°C, 10°C to 25°C, 30°C to 50°C, among others.
[0062] In some embodiments, the multi-stage polymer (or multi-layer particle) has a single T of 0° C. or more, about 1° C. or more, about 2° C. or more, about 3° C. or more, about 4° C. or more, about 5° C. or more, about 6° C. or less, about 7° C. or less, about 8° C. or less, about 9° C. or less, about 10° C. or less, or any value encompassed by these endpoints, as measured using differential scanning calorimetry (DSC). g The glass transition temperature can be determined by differential scanning calorimetry (DSC) by measuring the midpoint temperature using ASTM D 3418-12e1.
[0063] In some embodiments, Feed 1 may include an acrylic copolymer. The acrylic copolymer includes a copolymer derived from one or more (meth)acrylate monomers. The acrylic copolymer may be a pure acrylic polymer (i.e., a copolymer derived primarily from (meth)acrylate monomers), a styrene acrylic polymer (i.e., a copolymer derived from styrene and one or more (meth)acrylate monomers), or a vinyl acrylic polymer (i.e., a copolymer derived from one or more vinyl ester monomers and one or more (meth)acrylate monomers).
[0064] Feed 1 may include one or more soft ethylenically unsaturated monomers as well as one or more hard ethylenically unsaturated monomers.
[0065] As used herein, the term "soft ethylenically unsaturated monomer" refers to an ethylenically unsaturated monomer that, when homopolymerized, forms a polymer having a glass transition temperature of 0° C. or less as measured using differential scanning calorimetry (DSC). Soft ethylenically unsaturated monomers are known in the art and include, for example, ethyl acrylate (T g =-24℃), butyl acrylate (n-butyl acrylate, T g =-54℃), sec-butyl acrylate (T g =-26℃), sec-butyl acrylate (T g =-26℃), isobutyl acrylate (T g =-24℃), n-hexyl acrylate (T g =-45℃), n-hexyl methacrylate (T g =-5℃), 2-ethylhexyl acrylate (T g =-85℃), 2-ethylhexyl methacrylate (T g =-10℃), octyl methacrylate (T g =-20℃), n-decyl methacrylate (T g =-30℃), isodecyl acrylate (T g =-55℃), dodecyl acrylate (T g =-3℃), dodecyl methacrylate (T g =-65℃), 2-ethoxyethyl acrylate (T g =-50℃), 2-methoxyacrylate (T g =-50°C), and 2-(2-ethoxyethoxy)ethyl acrylate (T g =-70℃).
[0066] In some embodiments, Feed 1 may include soft ethylenically unsaturated monomers that, when homopolymerized, form a polymer with a glass transition temperature of about -30°C or higher, about -25°C or higher, about -24°C or higher, about -23°C or higher, about -22°C or higher, about -21°C or higher, about -20°C or higher, about -19°C or lower, about -18°C or lower, about -17°C or lower, about -16°C or lower, about -15°C or lower, about -10°C or lower, or any value encompassed by these endpoints, as measured by ASTM D3418-15, as measured using DSC. g can be, inter alia, from about -25°C to about -15°C, from about -18°C to about -10°C, from about -22°C to about -15°C.
[0067] In certain embodiments, the soft ethylenically unsaturated monomer may be a (meth)acrylate monomer. In certain embodiments, Feed 1 may include a soft ethylenically unsaturated monomer selected from the group consisting of butyl acrylate, 2-ethylhexyl acrylate, and combinations thereof.
[0068] Feed 1 may comprise at least 50% by weight (e.g., at least 50% by weight, at least 55% by weight, at least 60% by weight, at least 65% by weight, at least 70% by weight, at least 75% by weight, or at least 80% by weight, at least 85% by weight, at least 90% by weight, at least 95% by weight, at least 97% by weight, at least 99% by weight, or at least 99.9% by weight) of one or more soft ethylenically unsaturated monomers, based on the total weight of monomers used in Feed 1.
[0069] Feed 1 may contain an amount of one or more soft ethylenically unsaturated monomers ranging from any percentage above to any other percentage above. For example, Feed 1 may contain 50% to 99.9% by weight (e.g., 90% to 97% by weight, 50% to 85% by weight, 70% to 99% by weight, for example) of one or more soft ethylenically unsaturated monomers based on the total weight of monomers used.
[0070] Exemplary acrylate and methacrylate monomers include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, 2-methylheptyl (meth)acrylate, octyl (meth)acrylate, and the like. acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, alkyl crotonate, vinyl acetate, di-n-butyl maleate, di-octyl maleate acrylate, hydroxyethyl (meth)acrylate, allyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxy (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-propylheptyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, caprolactone (meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol (meth)acrylate, benzyl (meth)acrylate, hydroxypropyl (meth)acrylate, methyl polyglycol (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 1,6 hexanediol di(meth)acrylate, 1,4 butanediol di(meth)acrylate, and combinations thereof. In some embodiments, Feed 1 may include one or more acrylate monomers selected from the group consisting of methyl methacrylate, butyl acrylate, and 2-ethylhexyl acrylate.
[0071] Feed 1 may also include hard ethylenically unsaturated monomers. Suitable hard ethylenically unsaturated monomers include methyl methacrylate, T g = 125°C.
[0072] Methyl methacrylate may be present in the composition in an amount of about 30% by weight or more, about 35% by weight or more, about 40% by weight or less, about 45% by weight or less, about 50% by weight or less, or any value or range subsumed between these endpoints, for example, 30-50% by weight, or 35-45% by weight, based on the total weight of monomers used.
[0073] Feed 1 may include one or more carboxylic acid-containing monomers, based on the total weight of the monomers. Suitable carboxylic acid-containing monomers are known in the art and include α,β-monoethylenically unsaturated mono- and dicarboxylic acids, such as acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, dimethacrylic acid, ethylacrylic acid, allylacetic acid, vinylacetic acid, mesaconic acid, methylenemalonic acid, citraconic acid, and combinations thereof.
[0074] Feed 1 may contain 0 wt% or more (e.g., at least 0.5 wt%, at least 1 wt%, at least 1.5 wt%, at least 2 wt%, at least 2.5 wt%, at least 3 wt%, at least 3.5 wt%, at least 4 wt%, or at least 4.5 wt%) of one or more carboxylic acid-containing monomers based on the total weight of monomers used. Feed 1 may contain 5% or less (by weight) (e.g., 4.5% or less (by weight), 4% or less (by weight), 3.5% or less (by weight), 3% or less (by weight), 2.5% or less (by weight), 2% or less (by weight), 1.5% or less (by weight), 1% or less (by weight), or 0.5% or less (by weight)) of one or more carboxylic acid-containing monomers based on the total weight of monomers used.
[0075] Feed 1 may contain amounts of one or more carboxylic acid-containing monomers ranging from any of the minimum percentages above to any of the maximum percentages above. For example, Feed 1 may contain 0 wt% to 5 wt% (e.g., 0 wt% to 2.5 wt% of one or more carboxylic acid-containing monomers) based on the total weight of monomers used. In certain embodiments, Feed 1 may contain 0 wt% to 5 wt% (e.g., 0 wt% to 3 wt%, 0 wt% to 2.5 wt%, or 0 wt% to 1.5 wt%) of itaconic acid.
[0076] Feed 1 may be substantially free of styrene. In other words, the amount of styrene in Feed 1 may be 1 wt% or less, 0.5 wt% or less, 0.1 wt% or less, or 0 wt%.
[0077] Feed 2 may form a homopolymer derived from a single ethylenically unsaturated monomer or may form a copolymer derived from an ethylenically unsaturated monomer. In some embodiments, Feed 2 may include an acrylic polymer. Acrylic polymers include polymers derived from one or more (meth)acrylate monomers. In certain embodiments, the polymer formed from Feed 2 may have ethylenically unsaturated bonds.
[0078] Feed 2 may include one or more ethylenically unsaturated monomers. As used herein, the term "ethylenically unsaturated monomer" refers to a monomer that, when homopolymerized, has a T above 0° C. as measured using DSC. g Ethylenically unsaturated monomers are known in the art and include, for example, methyl acrylate (T g =10℃), methyl methacrylate (T g =120℃), ethyl methacrylate (T g =65℃), butyl methacrylate (T g =20℃), tert-butyl methacrylate (T g =118℃), isobutyl methacrylate (Tg =53℃), vinyl acetate (T g =30℃), hydroxyethyl acrylate (T g =15℃), hydroxyethyl methacrylate (T g =57℃), cyclohexyl acrylate (T g =19℃), cyclohexyl methacrylate (T g =92℃), 2-ethoxyethyl methacrylate (T g =16℃), 2-phenoxyethyl methacrylate (T g =54℃), benzyl acrylate (T g =6℃), benzyl methacrylate (T g =54℃), hydroxypropyl methacrylate (T g =76℃), styrene (T g =100℃), acrylamide (T g =165℃), acrylonitrile (T g =125°C), n-tert-butylacrylamide (T g =128℃), isobornyl acrylate (T g =94℃), isobornyl methacrylate (T g =110°C), and combinations thereof.
[0079] In some embodiments, Feed 2, upon homopolymerization, has a T of at least 80° C. (e.g., at least 85° C., at least 90° C., at least 95° C., at least 100° C., at least 105° C., at least 110° C., at least 115° C., or at least 120° C.) as measured using DSC. g The copolymer may include one or more ethylenically unsaturated monomers that form a polymer having the formula:
[0080] In some embodiments, Feed 2 can include 50% or more by weight of one or more ethylenically unsaturated monomers (e.g., 65% or more, 75% or more, 80% or more, 85% or more, 88% or more, 90% or more, 91% or more, 92% or more, 93% or more, 94% or more, or 95% or more by weight of ethylenically unsaturated monomers) based on the total weight of monomers used.
[0081] In some embodiments, Feed 2 may include one or more ethylenically unsaturated monomers selected from the group consisting of methyl methacrylate, butyl acrylate, and 2-ethylhexyl acrylate, and combinations thereof. In certain embodiments, Feed 2 may include at least 10% (e.g., at least 10% by weight, at least 20% by weight, at least 30% by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 92% by weight, at least 95% by weight, at least 96% by weight, at least 97% by weight, or at least 98% by weight) of one or more ethylenically unsaturated monomers selected from the group consisting of methyl methacrylate, butyl acrylate, and 2-ethylhexyl acrylate, and combinations thereof, based on the total weight of monomers used.
[0082] Feed 2 may be substantially free of styrene. In other words, the amount of styrene in Feed 2 may be 1 wt% or less, 0.5 wt% or less, 0.1 wt% or less, or 0 wt%.
[0083] In addition to the ethylenically unsaturated monomers, Feed 2 may also contain one or more ethylenically unsaturated acid monomers.
[0084] In some embodiments, Feed 2 may include one or more carboxylic acid-containing monomers based on the total weight of the monomers. Suitable carboxylic acid-containing monomers are known in the art and include α,β-monoethylenically unsaturated mono- and dicarboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, crotonic acid, maleic acid, fumaric acid, dimethacrylic acid, ethylacrylic acid, allylacetic acid, vinylacetic acid, mesaconic acid, methylenemalonic acid, citraconic acid, and combinations thereof.
[0085] Feed 2 may contain 0 wt% or more (e.g., at least 0.5 wt%, at least 1 wt%, at least 1.5 wt%, at least 2 wt%, at least 2.5 wt%, at least 3 wt%, at least 3.5 wt%, at least 4 wt%, or at least 4.5 wt%) of one or more carboxylic acid-containing monomers based on the total weight of monomers used. Feed 2 may contain 5% or less (by weight) (e.g., 4.5% or less (by weight), 4% or less (by weight), 3.5% or less (by weight), 3% or less (by weight), 2.5% or less (by weight), 2% or less (by weight), 1.5% or less (by weight), 1% or less (by weight), or 0.5% or less (by weight)) of one or more carboxylic acid-containing monomers based on the total weight of monomers used.
[0086] Feed 2 may contain an amount of one or more carboxylic acid-containing monomers ranging from any of the minimum percentages above to any of the maximum percentages above. For example, Feed 2 may contain 0 wt. % to 5 wt. % of one or more carboxylic acid-containing monomers (e.g., 0 wt. % to 2.5 wt. % of one or more carboxylic acid-containing monomers) based on the total weight of monomers used. In certain embodiments, Feed 2 may contain 0 wt. % to 5 wt. % (e.g., 0 wt. % to 3 wt. %, 0 wt. % to 2.5 wt. %, or 0 wt. % to 1.5 wt. %) of itaconic acid.
[0087] The copolymer formed from Feed 2 can have an acid content of about 5% or less, about 4% or less, about 3% or less, about 2% or less, about 1% or less, about 0.5% or less by weight, based on the total weight of the second copolymer, or any value encompassed by these endpoints.
[0088] The weight ratio of the first copolymer to the second copolymer in the multi-stage particle can be in the range of 50:50 to 75:25, for example 50:50, 60:40, 70:30, 75:25, or any value encompassed by these endpoints.
[0089] The monomer of Feed 2 can be present in the multistage particles in an amount of about 2.5 wt% or more, e.g., about 5 wt% or more, about 10 wt% or more, about 15 wt% or more, about 20 wt% or less, about 25 wt% or less, about 30 wt% or less, about 35 wt% or less, about 40 wt% or less, or any value encompassed by these endpoints, e.g., about 2.5 wt% to about 40 wt%, about 10 wt% to about 25 wt%, about 5 wt% to about 15 wt%, or about 35 wt% to about 40 wt%, based on the total particle weight.
[0090] In certain embodiments, the emulsion-polymerized monomers may include a mixture of methyl methacrylate, butyl acrylate, 2-ethylhexyl acrylate, and additional functional monomers such as acrylic acid, methylacrylic acid, and / or itaconic acid.
[0091] In certain embodiments, the amount of methyl methacrylate monomer present in the emulsion polymerization mixture, as a percentage of the total emulsion polymerization mixture, can be about 40% by weight or more, about 41% by weight or more, about 42% by weight or more, about 43% by weight or more, about 44% by weight or more, about 45% by weight or more, about 46% by weight or less, about 47% by weight or less, about 48% by weight or less, about 49% by weight or less, about 50% by weight or less, or any value encompassed by these endpoints.
[0092] In certain embodiments, the amount of butyl acrylate monomer present in the emulsion polymerization mixture, as a percentage of the total emulsion polymerization mixture, can be about 30% by weight or more, about 31% by weight or more, about 32% by weight or more, about 33% by weight or more, about 34% by weight or more, about 35% by weight or more, about 36% by weight or less, about 37% by weight or less, about 38% by weight or less, about 39% by weight or less, about 40% by weight or less, or any value encompassed by these endpoints.
[0093] In certain embodiments, the amount of 2-ethylhexyl acrylate monomer present in the emulsion polymerization mixture, as a percentage of the total emulsion polymerization mixture, can be about 5% by weight or more, about 10% by weight or more, about 15% by weight or more, about 20% by weight or less, about 25% by weight or less, about 30% by weight or less, or any value encompassed by these endpoints.
[0094] In certain embodiments, the emulsion polymerization mixture may include one or more functional monomers. The functional monomers may include one or more of acrylic acid monomers, methylacrylic acid monomers, and itaconic acid monomers. The functional monomer may be present in the emulsion polymerization mixture in an amount, as a percentage of the total emulsion polymerization mixture, of 0 wt% or more, about 0.1 wt% or more, about 0.2 wt% or more, about 0.3 wt% or more, about 0.4 wt% or more, about 0.5 wt% or more, about 0.6 wt% or more, about 0.7 wt% or more, about 0.8 wt% or more, about 0.9 wt% or more, about 1.0 wt% or less, about 1.1 wt% or less, about 1.2 wt% or less, about 1.3 wt% or less, about 1.4 wt% or less, about 1.5 wt% or less, about 1.6 wt% or less, about 1.7 wt% or less, about 1.8 wt% or less, about 1.9 wt% or less, about 2.0 wt% or less, or any value encompassed by these endpoints.
[0095] Feeds 1 and 2 can be fed to the reaction mixture for a period of about 60 minutes or more, about 70 minutes or more, about 80 minutes or more, about 90 minutes or less, about 100 minutes or less, about 110 minutes or less, about 120 minutes or less, or any value encompassed by these endpoints.
[0096] Feeds 1 and 2 may be fed to the reaction mixture at a temperature of about 60° C. or greater, about 65° C. or greater, about 70° C. or less, about 75° C. or less, about 80° C. or less, or any value encompassed by these endpoints.
[0097] The weight ratio of feed 1 to feed 2 monomers can be about 50:50 or more, about 55:45 or more, about 60:40 or more, about 65:35 or less, about 70:30 or less, about 75:25 or less, about 80:20 or less, or any value encompassed by these endpoints.
[0098] In certain embodiments, a surfactant may be present. Suitable surfactants may include, for example, Aerosol OT75. The amount of surfactant present in the emulsion polymerization mixture, as a percentage of the total emulsion polymerization mixture, can include 0 wt% or more, about 0.1 wt% or more, about 0.2 wt% or more, about 0.3 wt% or more, about 0.4 wt% or more, about 0.5 wt% or more, about 0.6 wt% or more, about 0.7 wt% or more, about 0.8 wt% or more, about 0.9 wt% or more, about 1.0 wt% or less, about 1.1 wt% or less, about 1.2 wt% or less, about 1.3 wt% or less, about 1.4 wt% or less, about 1.5 wt% or less, about 1.6 wt% or less, about 1.7 wt% or less, about 1.8 wt% or less, about 1.9 wt% or less, about 2.0 wt% or less, or any value encompassed by these endpoints.
[0099] The average diameter of the multi-layered particles, as determined by dynamic light scattering, can be about 100 nm or more, about 150 nm or more, about 200 nm or more, about 250 nm or more, about 300 nm or more, about 350 nm or less, about 400 nm or less, about 450 nm or less, about 500 nm or less, about 550 nm or less, about 600 nm or less, or any value encompassed by these endpoints.
[0100] The solids content of the emulsion can be about 25% or more, about 30% or more, about 35% or more, about 40% or less, about 45% or less, about 48% or less, about 50% or less, or any value inclusive of these endpoints.
[0101] The pH of the emulsion can be about 7.5 or more, about 7.6 or more, about 7.7 or more, about 7.8 or more, about 7.9 or more, about 8.0 or more, about 8.1 or more, about 8.2 or less, about 8.3 or less, about 8.4 or less, about 8.5 or less, about 8.6 or less, about 8.7 or less, about 8.8 or less, about 8.9 or less, about 9.0 or less, or any value inclusive of these endpoints.
[0102] The emulsion may be substantially free of grit. In other words, the amount of grit in the emulsion may be about 1% or less, about 0.9% or less, about 0.8% or less, about 0.7% or less, about 0.6% or less, about 0.5% or less, about 0.4% or less, about 0.3% or less, about 0.2% or less, or about 0.1% or less. The amount of grit may be determined by filtering 100 grams of the emulsion using a 125 or 45 micron filter, flushing with water, drying in an oven, and then weighing the amount of grit.
[0103] The emulsion may be stable under storage conditions. The stability of the emulsion may be determined, among other factors, by measuring the amount of coagulation present after a storage period. The degree of coagulation may be determined by molecular weight analysis after a storage period, as further described in the Examples below. The stability of the emulsion may also be determined by measuring the acid number after a storage period, as further described in the Examples below.
[0104] Suitable test periods can be, for example, about 1 week or more, about 2 weeks or more, about 3 weeks or more, about 4 weeks or more, or about 5 weeks or more. The temperature during the storage test period can be, for example, about 50°C.
[0105] Aqueous compositions comprising one or more of the above multi-stage polymers (or multi-layer particles) are also provided. The aqueous compositions may further comprise one or more additives, including pigments, fillers, dispersants, coalescents, defoamers, surfactants, thickeners, biocides, and combinations thereof. The choice of additives in the composition is influenced by many factors, including the nature of the multi-stage polymer (or multi-layer particles) dispersed in the aqueous composition, as well as the intended use of the composition. In some cases, the composition may be a coating composition, including, for example, a food-safety compatible coating composition. In some embodiments, the composition comprises 50 grams / liter or less of volatile organic compounds.
[0106] The aqueous composition may contain more than 40% solids, such as about 40% or more, about 50% or more, about 55% or more, about 60% or more, about 65% or more, or about 70% or more.
[0107] In some embodiments, the aqueous composition can further include one or more surfactants.Suitable surfactants can include, for example, Disonil A1080, Calfax DB45, Dowfax 2A-1, Aeorosol OT 75 (sodium dioctyl sulfosuccinate), and combinations thereof.
[0108] The composition can comprise 0 wt.% or more (e.g., 0 wt.%, at least 0.5 wt.%, at least 1 wt.%, at least 1.5 wt.%, at least 2 wt.%, at least 2.5 wt.%, at least 3 wt.%, at least 3.5 wt.%, at least 4 wt.%, at least 4.5 wt.%, at least 5 wt.%, at least 5.5 wt.%, at least 6 wt.%, at least 6.5 wt.%, at least 7 wt.%, at least 7.5 wt.%, at least 8 wt.%, at least 8.5 wt.%, at least 9 wt.%, or at least 9.5 wt.%) of one or more surfactants, based on the total weight of all components of the aqueous composition. The composition can comprise 10% or less (by weight) (e.g., 9.5% or less (by weight), 8% or less (by weight), 8.5% or less (by weight), 8% or less (by weight), 7.5% or less (by weight), 7% or less (by weight), 6.5% or less (by weight), 6% or less (by weight), 5.5% or less (by weight), 5% or less (by weight), 4.5% or less (by weight), 4% or less (by weight), 3.5% or less (by weight), 3% or less (by weight), 2.5% or less (by weight), 2% or less (by weight), 1.5% or less (by weight), 1% or less (by weight), or 0.5% or less (by weight)) of one or more surfactants, based on the total weight of all components of the aqueous composition.
[0109] The composition can include one or more surfactants in an amount ranging from any minimum percentage above to any maximum percentage above. For example, the composition can include 0% to 10% by weight of one or more surfactants (e.g., 0% to 3% by weight of one or more surfactants, 0% to 2.5% by weight of one or more surfactants, 0% to 1.5% by weight of one or more surfactants, or 0% to 1% by weight of one or more surfactants), based on the total weight of all components of the aqueous composition. In some embodiments, the composition is substantially free of surfactants (i.e., the composition includes 0.1% or less (by weight)).
[0110] Examples of suitable pigments include metal oxides such as titanium dioxide, zinc oxide, iron oxide, or combinations thereof. In certain embodiments, the composition comprises a titanium dioxide pigment. Examples of commercially available titanium dioxide pigments are KRONOS® 2101, KRONOS® 2310, available from Kronos WorldWide, Inc. (Cranbury, NJ), TI-PURE® R-900, available from DuPont (Wilmington, DE), or TIONA® AT1, available from Millenium Inorganic Chemicals. Titanium dioxide is also available in concentrated dispersion form. An example of a titanium dioxide dispersion is KRONOS® 4311, also available from Kronos WorldWide, Inc.
[0111] Examples of suitable fillers include calcium carbonate, nepheline shenite, (25% nepheline, 55% sodium feldspar and 20% potassium feldspar), feldspar (aluminosilicate), diatomaceous earth, calcined diatomaceous earth, talc (hydrated magnesium silicate), aluminosilicate, silica (silicon dioxide), alumina (aluminum oxide), clay, (hydrated aluminum silicate), kaolin (kaolinite, hydrated aluminum silicate), mica (hydrated potassium aluminum silicate), pyrophyllite (aluminum hydroxide silicate), perlite, barite (barium sulfate), wollastonite (calcium metasilicate), and combinations thereof. In certain embodiments, the composition comprises a calcium carbonate filler.
[0112] Examples of suitable dispersants are polyacid dispersants and hydrophobic copolymer dispersants.Polyacid dispersants are typically polycarboxylic acids such as polyacrylic acid or polymethacrylic acid, partially or completely in the form of their ammonium, alkali metal, alkaline earth metal, ammonium or lower alkyl quaternary ammonium salts.Hydrophobic copolymer dispersants include copolymers of acrylic acid, methacrylic acid or maleic acid with hydrophobic monomers.In certain embodiments, the composition comprises a polyacrylic acid type dispersant, such as Pigment Disperser N, available from BASF SE.
[0113] Suitable coalescents that aid in film formation during drying include ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether, diethylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, and combinations thereof.
[0114] Examples of suitable thickeners include hydrophobically modified ethylene oxide urethane (HEUR) polymers, hydrophobically modified alkali soluble emulsion (HASE) polymers, hydrophobically modified hydroxyethyl cellulose (HMHEC), hydrophobically modified polyacrylamides, and combinations thereof. HEUR polymers are linear reaction products of diisocyanates and polyethylene oxide end-capped with hydrophobic hydrocarbon groups. HASE polymers are homopolymers of (meth)acrylic acid or copolymers of (meth)acrylic acid, (meth)acrylate esters, or maleic acid modified with hydrophobic vinyl monomers. HMHEC includes hydroxyethyl cellulose modified with hydrophobic alkyl chains. Hydrophobically modified polyacrylamides include copolymers of acrylamide and acrylamide (N-alkylacrylamide) modified with hydrophobic alkyl chains. In certain embodiments, the coating composition includes a hydrophobically modified hydroxyethyl cellulose thickener.
[0115] Defoamers serve to minimize foaming during mixing and / or application of coating compositions. Suitable defoamers include silicone oil defoamers such as polysiloxanes, polydimethylsiloxanes, polyether modified polysiloxanes, and combinations thereof. Exemplary silicone-based defoamers include BYK®-035 available from BYK USA Inc. (Wallingford, Connecticut), TEGO® series defoamers available from Evonik Industries (Hopewell, Virginia), and DREWPLUS® series defoamers available from Ashland Inc. (Covington, Kentucky).
[0116] Suitable surfactants include nonionic surfactants and anionic surfactants. Examples of nonionic surfactants are alkylphenoxypolyethoxyethanols having an alkyl group of about 7 to about 18 carbon atoms and having about 6 to about 60 oxyethylene units; ethylene oxide derivatives of long chain carboxylic acids; similar ethylene oxide condensates of long chain alcohols, and combinations thereof. Exemplary anionic surfactants include ammonium, alkali metal, alkaline earth metal, and lower alkyl quaternary ammonium salts of sulfosuccinates, higher fatty alcohol sulfates, aryl sulfonates, alkyl sulfonates, alkylaryl sulfonates, and combinations thereof. In certain embodiments, the composition comprises a nonionic alkyl polyethylene glycol surfactant, such as LUTENSOL® TDA 8 or LUTENSOL® AT-18, commercially available from BASF SE. In certain embodiments, the composition comprises an anionic alkyl ether sulfate surfactant. In certain embodiments, the composition comprises an anionic diphenyl oxide disulfonate surfactant, such as CALFAX® DB-45, commercially available from Pilot Chemical. In some embodiments, the composition includes an anionic surfactant, such as Aeorosol OT75. In some embodiments, the composition is substantially free of sulfate surfactants (i.e., the composition includes 0.1% or less by weight). In some embodiments, the composition is substantially free of sulfonate surfactants (i.e., the composition includes 0.1% or less by weight). In some embodiments, the composition is substantially free of sulfate surfactants and sulfonate surfactants (i.e., the composition includes 0.1% or less by weight).
[0117] Suitable biocides can be incorporated to inhibit the growth of bacteria and other microorganisms in the coating composition during storage. Exemplary biocides include 2-[(hydroxymethyl)amino]ethanol, 2-[(hydroxymethyl)amino]2-methyl-1-propanol, o-phenylphenol, sodium salt, 1,2-benzisothiazolin-3-one, 2-methyl-4-isothiazolin-3-one (MIT), 5-chloro-2-methyl-4-isothiazolin-3-one (CIT), 2-octyl-4-isothiazolin-3-one (OTT), 4,5-dichloro-2-n-octyl-3-isothiazolone, and acceptable salts and combinations thereof. Suitable biocides also include moldicides that inhibit the growth of mold or its spores in the coating. Examples of fungicides include 2-(thiocyanomethylthio)benzothiazole, 3-iodo-2-propynyl butylcarbamate, 2,4,5,6-tetrachloroisophthalonitrile, 2-(4-thiazolyl)benzimidazole, 2-N-octyl 4-isothiazolin-3-one, diiodomethyl p-tolylsulfone, and acceptable salts and combinations thereof. In certain embodiments, the coating composition contains 1,2-benzisothiazolin-3-one or a salt thereof. This type of biocide includes PROXEL® BD20, available from Arch Chemicals, Inc. (Atlanta, Georgia).
[0118] Other suitable additives that may optionally be incorporated into the composition include rheology modifiers, wetting and spreading agents, leveling agents, conductive additives, adhesion promoters, antiblocking agents, anti-crush and anti-crawler agents, antifreeze agents, corrosion inhibitors, antistatic agents, flame retardants and intumescent additives, dyes, optical brighteners and fluorescent additives, UV absorbers and light stabilizers, chelating agents, detergency additives, crosslinking agents, leveling agents, flocculants, wetting agents, humectants, lubricants, odorants, oils, waxes and anti-skid agents, soil repellents, antifouling agents, and combinations thereof.
[0119] The coating composition can be applied to a surface by any suitable coating technique, including spraying, rolling, brushing, or spreading. The coating composition can be applied in a single coat or in multiple successive coats (e.g., two or three coats) as needed for a particular application. Generally, the coating composition is allowed to dry under ambient conditions. However, in certain embodiments, the coating composition can be dried, for example, by applying heat and / or circulating air over the coating.
[0120] The coating composition can be applied to a variety of surfaces including, but not limited to, paper, paperboard, and cardboard.
[0121] Also provided is a coating formed from the coating composition described herein. Generally, the coating is formed by applying the coating composition described herein to a surface and drying the coating to form the coating. The coating thickness can vary depending on the application of the coating.
[0122] One aspect of the claimed invention relates to a substrate comprising at least one surface coated with at least one layer comprising the aqueous composition disclosed herein. In one embodiment of the claimed invention, the substrate is paper or paperboard.
[0123] The aqueous compositions disclosed herein can be used with any substrate to provide resistance to water, moisture, grease, oil, and / or oxygen. In one embodiment of the claimed invention, the substrate can be a cellulosic substrate, such as paper, paperboard, or cardboard. Cellulosic substrates can be used in a wide variety of applications, including, for example, paper cups (including, for example, disposable or recyclable paper cups), dry food (e.g., coffee, tea, powdered soup, powdered sauce, etc.), liquid (e.g., cosmetics, cleaning products, beverages, etc.), tube laminates, paper carrier bags, paper laminates and coextrusions for ice cream, confectionery (e.g., chocolate bars, muesli bars), paper adhesive tapes, cardboard cups (e.g., paper cups), yogurt containers, soufflé cups, meal trays, or meat trays, rolled cardboard containers (e.g., cans, drums), exterior moisture resistant cartons (e.g., wine bottles, food), coated cardboard fruit boxes, fast food plates, clamp shells, beverage cartons, liquid cartons such as detergents and cleaning products, frozen food cartons, ice packaging (e.g., ice cups, cone-shaped ice cream wafer wrappers, etc.), paper labels, flower pots and plant containers. The container may contain a paper bag.
[0124] Another aspect of the claimed invention relates to a coated paper or article comprising the aqueous composition disclosed herein. In one embodiment of the claimed invention, the coated paper or article comprising the aqueous composition disclosed herein has a coating density of about 2 g / m 2 of the coated paper. 2 ~about 30 g / m 2 In one embodiment of the claimed invention, the coated paper or article comprising the aqueous composition disclosed herein has a coating weight in the range of about 10 g / m2 of the coated paper. 2 ~about 25 g / m 2In another embodiment of the claimed invention, the coated paper has a block resistance of 3 or greater at 60° C. and 60 psi for 24 hours, measured according to ASTM WK20008. In another embodiment of the claimed invention, the coated paper has a block resistance of 4 or greater at 60° C. and 60 psi for 24 hours, measured according to ASTM WK20008. In yet another embodiment of the claimed invention, the paper exhibits oil and / or grease resistance.
[0125] Another aspect of the claimed invention relates to a method of making paper comprising at least the step of contacting cellulosic fibers with an aqueous composition disclosed herein. In one embodiment of the claimed invention, the step of contacting the cellulosic fibers with the aqueous composition comprises coating a paper web comprising the cellulosic fibers with an aqueous dispersion comprising the aqueous composition. In another embodiment of the claimed invention, contacting the cellulosic fibers with the aqueous composition disclosed herein comprises (i) mixing the aqueous dispersion comprising the aqueous composition with the cellulosic fibers to form a slurry, and (ii) forming a paper web from the slurry of cellulosic fibers and the aqueous composition.
[0126] In another embodiment of the claimed invention, the aqueous composition is coated onto a substrate. For example, the aqueous composition may be provided as a coating on a paper web. The aqueous composition may be provided at a concentration of 2 g / m 2 or more, e.g. 3 g / m 2 more than 4 g / m 2 More than 5 g / m 2 more than 6 g / m 2 More than 7g / m 2 More than 8 g / m 2 More than 9 g / m 2 More than 10 g / m 2 More than 11 g / m 2 More than 12 g / m 2 More than 13 g / m 2 More than 14 g / m 2 More than 15 g / m 2 More than 16 g / m 2More than 17 g / m 2 More than 18 g / m 2 More than 19 g / m 2 More than 20 g / m 2 More than 21 g / m 2 More than 22 g / m 2 More than 23 g / m 2 More than 24 g / m 2 More than 25 g / m 2 More than 26 g / m 2 More than 27 g / m 2 More than 28 g / m 2 or 29 g / m 2 In one embodiment of the claimed invention, the aqueous composition can have a coating weight of 30 g / m or more. 2 For example, 29 g / m 2 Below 28 g / m 2 Below, 27 g / m 2 Below, 26 g / m 2 Below 25 g / m 2 Below 24 g / m 2 Below, 23 g / m 2 Below, 22 g / m 2 Below, 21 g / m 2 Below 20 g / m 2 Below, 19 g / m 2 Below 18 g / m 2 Below 17 g / m 2 Below 16 g / m 2 Below 15 g / m 2 Below 14 g / m 2 Below, 13 g / m 2 Below, 12 g / m 2 Below, 11 g / m 2 Below 10 g / m 2 Below, 9 g / m 2 Below 8 g / m 2 Below, 7 g / m 2 Below 6 g / m 2 Below 5 g / m 2 Below 4 g / m 2 or less than 3 g / m 2In yet another embodiment of the claimed invention, the aqueous composition may have a coating weight of 2 g / m 2 ~30 g / m 2 , e.g. 3 g / m 2 ~30 g / m 2 , 4 g / m 2 ~30 g / m 2 , 5 g / m 2 ~30 g / m 2 , or 10 g / m 2 ~25 g / m 2 The coating weight can be reported in units of grams of coating per square meter of cellulosic substrate and can be calculated directly by the amount of coating applied and the surface area of the cellulosic substrate to which the coating is applied. In one embodiment of the claimed invention, the aqueous composition can be applied in an amount of less than 15 wt. % based on the weight of the coated cellulosic substrate. In some embodiments, the aqueous composition can be 0.01 wt. % to 5 wt. %, e.g., 0.1 wt. % to 5 wt. %, 0.5 wt. % to 5 wt. %, 0.1 wt. % to 4 wt. %, 0.1 wt. % to 3 wt. %, 0.1 wt. % to 2.5 wt. %, or 0.1 wt. % or more, 0.5 wt. % or more, 1 wt. % or more, 1.5 wt. % or more, based on the weight of the substrate.
[0127] In one embodiment of the claimed invention, the aqueous composition can have a thickness of 0.40 mils or more, e.g., 0.5 mils or more, 0.6 mils or more, 0.7 mils or more, 0.8 mils or more, 0.9 mils or more, 1 mil or more, 1.1 mils or more, 1.2 mils or more, 1.3 mils or more, 1.4 mils or more, 1.5 mils or more, 1.6 mils or more, 1.7 mils or more, 1.8 mils or more, 1.9 or more. In one embodiment of the claimed invention, the aqueous composition can have a thickness of 2 mils or less, e.g., 1.9 mils or less, 1.8 mils or less, 1.7 mils or less, 1.6 mils or less, 1.5 mils or less, 1.4 mils or less, 1.3 mils or less, 1.2 mils or less, 1 mils or less, 0.9 mils or less, 0.8 mils or less, 0.7 mils or less, 0.6 mils or less, or 0.5 mils or less. The aqueous composition, in some embodiments, can have a thickness of 0.4 mils to 2 mils, such as 0.5 mils to less than 1.8 mils, 0.6 mils to 1.6 mils, or 0.7 mils to 1.5 mils. The coating thickness can be calculated based on the density of the coating and the weight of the coated cellulosic substrate.
[0128] In one embodiment of the claimed invention, the coating is provided with an aqueous composition. In another embodiment of the claimed invention, the coating can be on one or more surfaces of the substrate. For the purposes of the claimed invention, the substrate also refers to a paper cup or a paper bag. The paper cup can have an inner surface, an outer surface, a bottom, and a side. The aqueous composition can be on a first surface and / or a second surface of the paper cup. The first surface can include one or more of the inner surface of the side and / or the inner surface of the bottom. In some embodiments, only a portion of the inner surface is coated, for example, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or all of the inner surface. In one embodiment of the claimed invention, the entire inner surface is coated. In one embodiment of the claimed invention, the second surface includes one or more of the outer surface of the side and / or the outer surface of the bottom. In other embodiments of the claimed invention, only a portion of the exterior surface is coated, such as 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or all of the exterior surface is coated. In yet other embodiments of the claimed invention, the entire exterior surface is coated.
[0129] The aqueous composition can be coated onto the cellulosic substrate using a paper machine in a mill or printing process.
[0130] In one embodiment of the claimed invention, the aqueous composition is provided to a substrate, such as a paper web formed of cellulosic fibers. In yet another embodiment of the claimed invention, the aqueous composition may be from 4% to 30% by weight, such as 5% to 30% by weight, 5% to 29% by weight, 5% to 28% by weight, 5% to 27% by weight, 5% to 26% by weight, 5% to 20% by weight, or 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, or 10% or more by weight, in each case based on the weight of the substrate.
[0131] The aqueous composition may be added to a substrate, such as a cellulosic substrate, using any method known in the art for adding an aqueous composition to a substrate. In one embodiment of the claimed invention, the method can include coating a paper web comprising cellulosic fibers with an aqueous dispersion comprising the aqueous composition. In another embodiment of the claimed invention, the method can include spraying the aqueous dispersion comprising the aqueous composition onto the paper web. In yet another embodiment of the claimed invention, the method can include mixing the aqueous dispersion comprising the aqueous composition with an aqueous slurry comprising cellulosic fibers to form a mixture, and forming a paper web from the mixture of cellulosic fibers and the aqueous composition.
[0132] In one embodiment of the claimed invention, the aqueous composition can impart water, moisture, grease, oil and / or oxygen resistance to the substrate compared to applications without the aqueous composition. The substrate can also exhibit reduced or eliminated leakage or contamination. Liquid water and water vapor resistance of substrates containing the aqueous composition can be tested by the Cobb method described in TAPPI T 441 (2001), which is incorporated herein by reference in its entirety. This method determines the amount of liquid water or water vapor absorbed by paper, paperboard, and corrugated board in a specified time under standardized conditions. In one embodiment of the claimed invention, the coated substrates described herein pass the water resistance test described in this test method. Water absorption can be a function of various properties of the paper or paperboard, including but not limited to sizing and porosity.
[0133] In one embodiment of the claimed invention, over a period of 30 minutes, the substrate containing the aqueous composition is coated with a coating weight of about 10 g / m2 as determined by Tappi T441. 2 More than about 12 g / m 2 More than about 14 g / m 2 More than about 16 g / m 2 More than about 18 g / m 2 More than about 20 g / m 2 Below, approximately 22 g / m 2Below, approximately 24 g / m 2 Below, approximately 26 g / m 2 Below about 30 g / m 2 The following Cobb values, or any values encompassed by these endpoints, can be indicated.
[0134] Additionally, substrates comprising the aqueous compositions described herein may exhibit minimal tendency to block, i.e., adhesion of a coated surface to another coated surface, or adhesion of a coated surface to an uncoated surface of an extrusion coated paper when wound onto a paper roll, prior to cutting / forming into a final paper product. Blocking resistance may be tested using an ICBlock tester as described in ASTM WK20008.
[0135] By way of non-limiting illustration, examples of specific embodiments of the present disclosure are provided below. EXAMPLES
[0136] Aspects of the present claimed invention are more fully described by the following examples, which are set forth to illustrate certain aspects of the invention and are not to be construed as limitations thereof.
[0137] material: The monomer abbreviations used in the aqueous compositions are as follows:
[0138] AA is the abbreviation for acrylic acid, obtained from Aldrich Chemical Company.
[0139] BA is an abbreviation for n-butyl acrylate that was obtained from Aldrich Chemical Company.
[0140] MAA is an abbreviation for methacrylic acid that was obtained from Aldrich Chemical Company.
[0141] MMA is the abbreviation for methyl methacrylate, obtained from Aldrich Chemical Company.
[0142] AMS is alpha-methylstyrene obtained from Aldrich Chemical Company.
[0143] 2-EHA is an abbreviation for 2-ethylhexyl acrylate that was obtained from Aldrich Chemical Company.
[0144] STY is an abbreviation for styrene obtained from Aldrich Chemical Company.
[0145] APS is an abbreviation for ammonium persulfate obtained from Aldrich Chemical Company; and
[0146] TBHP is an abbreviation for tert-butyl hydroperoxide, obtained from Aldrich Chemical Company.
[0147] Isoascorbic acid is obtained from Aldrich Chemical Company.
[0148] Filtrez™ 530 is an alcohol soluble fumaric acid modified rosin ester with a high softening point and high acid number, Tg=105.8° C.; acid number=195 mg KOH / gram; viscosity G by Gardner-Holdt (2.3 seconds), 60% NV ethanol, 25° C.; Mn=656 Da.; Mw=2011 Da.; PDI=3.07, available from Lawter.
[0149] Filtrez™ 531 is an alcohol soluble fumaric acid modified rosin ester with a high softening point and moderately high acid number (Tg=105° C.); acid number=176 mg KOH / gram; viscosity L by Gardner-Holdt (3.6 sec), 60% NV ethanol, 25° C.; Mn=746 Da.; Mw=3636 Da.; PDI=4.87, available from Lawter.
[0150] Filtrez™ 3320 is a maleic acid modified rosin ester with melting point=123° C.; acid number=64 mg KOH / gram; viscosity D (1.4 sec by Gardner-Holdt, 60% NV toluene, 25° C.); Mn=875 Da.; Mw=2516 Da.; PDI=2.88, available from Lawter.
[0151] Filtrez™ 5014A is an alcohol soluble fumaric acid modified rosin ester with Tg=85° C.; acid number=175 mg KOH / gram; viscosity J by Gardner-Holdt (3.1 sec), 60% NV ethanol, 25° C.; Mn=760 Da.; Mw=6605 Da.; PDI=8.69, available from Lawter.
[0152] Calfax DB 45 is a C12 (branched) sodium diphenyloxide disulfonate available from Pilot.
[0153] Aerosol OT75 is a dioctyl sodium sulfosuccinate solution, a surfactant, available from Solvay.
[0154] Disponil AFX1080 is an alkylaryl polyglycol ether sulfate, ammonium salt, emulsifier available from BASF.
[0155] Test Method: Molecular weight determination: Gel permeation chromatography (GPC) spectra were obtained on a Waters 2695 instrument and used to measure the molecular weight of the polymers using tetrahydrofuran (THF) as the mobile phase and an RI detector at 40° C. All samples were analyzed for number average molecular weight (Mn), weight average molecular weight (Mw) and polydispersity (PDI) using elution times calibrated against polystyrene molecular weight standards.
[0156] Solids content measurements: The solids content of the dispersions was determined gravimetrically by drying about 0.5 g to about 2 g of a dispersion sample in a 140° C. oven for 1 hour.
[0157] Viscosity measurements: Viscosity was measured by Brookfield LV at 20°C to 25°C.
[0158] Particle size determination, including volume average particle size: The particle size of the dispersions was measured using a Nanoflex particle sizer manufactured by Microtrac.
[0159] Acid value determination: Acid value or acid number was determined by potentiometric titration according to ASTM D664-95.
[0160] Glass transition temperature measurements: Glass transition temperatures (Tg) were measured by differential scanning calorimetry (DSC) according to ASTM D3418-15.
[0161] Minimum film formation temperature (MFFT) determination: MFFT was measured according to ASTM D2354-10.
[0162] Block Resistance: Block resistance tests were measured according to ASTM WK20008. Block resistance tests were performed to determine the resistance of a polymeric binder under pressure and at elevated temperatures to stick to itself and to uncoated paper. The test measures the degree of sticking and damage sustained by a coated substrate when exposed to standard temperatures, pressures, and times. A roll of coated stock can achieve an internal pressure of up to 60 psi, depending on the uniformity of the paper. When stored or transported under tropical conditions (30°C and 95% relative humidity), the coated paper layers can stick together, and in a worst case scenario, the paper or coating can be significantly damaged. Block resistance tests were performed at 50°C and 60 psi for 24 hours. Samples were cut to 1x3 inches, and two sheets were laminated in a block test apparatus with coating-to-paper (face-to-back, FB) or coating-to-coating (face-to-face, FF). A spring was then placed on top of the layers to apply a constant amount of pressure to the sample. The entire device was placed in an oven with 50°C humid conditions for 24 hours. A Koehler Instrument K53000 IC block tester was used for this test. Once the block test was completed, the samples were removed and monitored for tack and damage. The evaluation system is described below.
[0163] Evaluation system for block resistance testing.
[0164] [Table 1]
[0165] Cobb Test. The Cobb test was measured according to TAPPI T 441 (2001). This method describes a procedure for determining the amount of water absorbed by nonabsorbent paper, paperboard and corrugated fiberboard in a specified time under standardized conditions. It is based on work by Cobb and Lowe, Cobb and other researchers. Water absorption is a function of various properties of the paper or paperboard such as sizing, porosity, etc. This method is generally applicable to sized paper, paperboard and corrugated fiberboard. Five (8.5" x 11") sheets are used to perform a suitable test. Generally, five replicate pieces of paper are tested.
[0166] Heat seal test. The heat seal test was measured according to ASTM F2029. A semi-automatic heat sealer was used to seal the samples according to ASTM F2029 at a specific temperature, pressure, and sealing time (e.g., 1 second dwell time, 40 psi, 125-250°C). A hot tack peel strength tester is used to determine the hot tack test of plastic films, laminated films and other packaging films. Meanwhile, it is also used for peel, shear, tensile and other test items of adhesives and laminated films.
[0167] Example 1: Synthesis of a polymer resin dispersion containing 35% fumaric acid modified rosin ester content using one monomer feed A reaction vessel equipped with a condenser, thermometer, nitrogen inlet and overhead stirrer was charged with deionized water (90.8 grams), Calfax DB45 (1.25 grams, 45% solids) and fumaric acid modified rosin ester dispersion (Filtrez 531, 506.5 grams, 28% solids) and heated to 70°C under a nitrogen flow. Isoascorbic acid (2.26 grams), ammonium hydroxide (1.12 grams, 29%) and deionized water (27.74 grams) were added and held with stirring for 2-3 minutes. Copper sulfate (0.02 grams) and deionized water (8.56 grams) were added and held with stirring for 3-5 minutes. The monomer feed mixture (methyl methacrylate MMA, 55.94 grams; n-butyl acrylate BA, 128.13 grams; Aerosol OT75, 4.62 grams (75% solids); and 2-ethylhexyl acrylate 2-EHA, 82.05 grams) was added over 100 minutes, followed by a flush with 2.85 grams of deionized water. The initiator feed (tertiary-butyl hydroperoxide (3.37 grams, 70 wt%) in 43.81 grams of deionized water) was started simultaneously with the monomer feed and continued for 100 minutes, followed by a 30 minute hold. Two separate solutions (sodium erythorbate, 19.27 grams, 12% solids in 1.5 g deionized water) and (tertiary-butyl hydroperoxide, 1.41 grams, 70 wt%, in 8.46 grams of deionized water) were added simultaneously over 60 minutes, followed by a 30 minute hold. The reaction mass was cooled to 30° C. and filtered. The desired aqueous polymeric resin dispersion containing 35% fumaric acid modified rosin ester content was obtained with the following properties: Solids=39.9 wt%; Tg=−26° C.; pH=8.6; Particle size (volume average diameter, dv)=222 nm; Mn=23.82 kDa Mw=69.72 kDa, PDI=2.97; Viscosity=28 cps.
[0168] Example 2: Synthesis of polymer resin dispersions containing various concentrations of fumaric acid modified rosin ester content using one monomer feed According to the synthesis procedure of Example 1, six different examples of aqueous polymer resin dispersions containing various concentrations of fumaric acid modified rosin ester content were synthesized, and the properties are shown in Table 1 below.
[0169]
Table 2
[0170] Example 3: Synthesis of a polymer resin dispersion containing 35% fumaric acid modified rosin ester content using two monomer feeds Deionized water (90.8 grams), Calfax DB45 (1.25 grams, 45% solids) and fumaric acid modified rosin ester dispersion (Filtrez 531, 503 grams, 28% solids) were added to a reaction vessel equipped with a condenser, thermometer, nitrogen inlet and overhead stirrer and heated to 70° C. under a nitrogen flow. Isoascorbic acid (2.19 grams), ammonium hydroxide (1.04 grams, 29%) and deionized water (26.06 grams) were added and held with stirring for 3 minutes. Copper sulfate (0.02 grams) and deionized water (8.56 grams) were added and held with stirring for 3 minutes. The first monomer mixture (methyl methacrylate MMA, 31.66 grams; n-butyl acrylate BA, 62.52 grams; Aerosol OT75, 2.28 grams (75% solids); and 2-ethylhexyl acrylate 2-EHA, 37.73 grams) was added over 50 minutes. After the first addition, the second monomer mixture (methyl methacrylate MMA, 84.42 grams; n-butyl acrylate BA, 34.3 grams; Aerosol OT75, 2.28 grams (75% solids); and 2-ethylhexyl acrylate 2-EHA, 13.19 grams) was added over 50 minutes, followed by a flush with 4.5 grams of deionized water. An initiator feed (tert-butyl hydroperoxide (3.28 grams, 70 wt%) in 42.7 grams of deionized water) was started simultaneously with the monomer feeds and continued for 100 minutes, followed by a 30 minute hold with stirring during post polymerization. Two separate solutions (19.27 grams of sodium erythorbate (12% solids) in 1.5 grams of deionized water) and (1.41 grams of tert-butyl hydroperoxide (70% by weight) in 8.43 grams of deionized water) were added simultaneously over 60 minutes, followed by a 30 minute hold. The reaction was cooled to 30° C. and filtered. The desired aqueous polymer resin dispersion containing 35% fumaric acid modified rosin ester content was obtained with the following properties: solids=40% by weight; Tg=6C; pH=8.7; particle size (volume average diameter, dv)=225 nm; Mn=28.65 kDa Mw=84.48 kDa, PDI=2.95; viscosity=34 cPs.
[0171] Example 4: Synthesis of a polymer resin dispersion containing 40% fumaric acid modified rosin ester content using two monomer feeds Following the procedure of Example 3, the desired polymer resin dispersion containing 40% fumaric acid modified rosin ester content was obtained with the following properties: solids=39.8 wt%; Tg=5C; pH=8.6; particle size (volume average diameter, dv)=180 nm; Mn=24.22 kDa Mw=73.12 kDa; PDI=3.02; viscosity=29 cPs.
[0172] Example 5: Redox Initiators Compared to Ammonium Persulfate Initiators As further described in Comparative Example 2 below, three emulsions were prepared using various amounts of rosin and different initiators, either tert-butyl hydroperoxide as the redox initiator or ammonium persulfate (APS) as the thermal initiator. The emulsions were processed at different temperatures depending on the initiator used. When using the thermal initiator, the reaction was warmed to 85° C. When using the redox initiator, the reaction was carried out at 70° C. The percent conversion over time was measured and is shown in Table 2. As shown therein, both preparations using the redox initiator achieved nearly complete conversion, while the preparation using APS reacted more slowly and did not reach 100% conversion.
[0173] [Table 3]
[0174] Example 6: Water absorption and block resistance as a function of rosin percentage Eight emulsion formulations were tested for effectiveness. The comparative examples contained styrene and the remaining examples did not contain styrene. Specifically, formulations containing various amounts of rosin ester were tested for water absorption and block resistance, and the results are shown in Table 3.
[0175] [Table 4]
[0176] As shown, formulations containing Feed 1 and Feed 2 monomers with 35 or 40% rosin, respectively, showed favorable results for water absorption and comparable results for blocking resistance.
[0177] Example 7: Water absorption and block resistance of coatings Two different styrene-free emulsions were formulated using rosin ester (35%). The multilayer particles exhibited a Tg of 5-7°C. The hydrophobic monomers used were methyl methacrylate, n-butyl acrylate, and 2-ethylhexyl acrylate in a weight ratio of 1:1.97:1.19. The monomer ratio was 50:50 feed 1 to feed 2. The initiator used was a redox initiator containing tert-butyl hydroperoxide (TBHP) and ascorbic acid. The polymerization temperature was 70°C. One emulsion contained acrylic acid (AA) as the functional monomer (rosin emulsion 1) and the other emulsion was prepared without any functional monomer (rosin emulsion 2). The emulsions were tested against standard emulsions on both SBS and C1S boards to determine water absorption and block resistance. The properties of the emulsions tested are shown in Table 4 below.
[0178] [Table 5]
[0179] The boards were coated using either a rod coating application or a flexo-anilox application. For rod coating, 1 / 0 rod was used at 5–8 g / m 2 A load of 1000 psi was used. The coatings were dried at 60°C for 1 minute and then conditioned at 50% relative humidity and 25°C for 1-4 days. The Cobb test was performed at room temperature for 30 minutes. Block resistance tests were performed at 50°C under 60 lbs force for 24 hours (coating to coating and coating to substrate).
[0180] For flexo anilox applications, the anilox used was 2 x 120 Lpi anilox with a loading of 6-7 g / m2. The flexo plates were dried at 80°C for 1 minute and then conditioned at 25°C and 50% relative humidity for 1-4 days. The Cobb test was performed at room temperature for 20 minutes and the blocking resistance test was performed as described for the rod coating application.
[0181] The water absorption and blocking resistance of SBS alone and C1S alone were tested on rod or flexo coated boards using the above formulations. The penetration and Cobb values of Rosin Emulsions 1 and 2 and the standard, along with the board and coating method used, are shown in Table 5 below.
[0182] [Table 6]
[0183] As shown in Table 5, the emulsions of the present disclosure match or improve upon currently available emulsions.
[0184] Example 8: Surface tension The above two rosin emulsions were then tested against standards to determine the total surface energy of the coating on SBS paperboard applied using either rod coating or flexographic methods. The results are shown in Table 6 below. As a reference, the surface tension of water is 72.8 mN / m (millinewtons per meter), the surface tension of Comparative Example 1 is 41.7 mN / m, and the surface tension of Rosin Emulsions 1 and 2 is about 34.5 mN / m.
[0185] [Table 7]
[0186] Example 9: Hydrolytic stability The two emulsion preparations were tested for hydrolytic stability at 50° C. Stability was determined by determining both the acid number and molecular weight after the indicated storage periods. The results are shown in Table 7 below.
[0187] [Table 8]
[0188] Example 10: Hydrolytic stability at 50°C storage Various waterborne polymer resins of the present invention were tested for hydrolytic stability at 50° C. Stability was determined by examination of settling, phase separation and coagulation after the indicated storage periods. The results are shown in Table 8 below. Grit % was determined at the end of the polymerization process as opposed to the end of the storage period. With respect to storage stability, a rating of good / stable indicates no clumping, no phase separation, and no settling.
[0189] [Table 9]
[0190] Example 11: Heat seal test Heat seal tests were performed according to ASTM F2029. Heat seal tests of rosin emulsion 2 were performed at different temperatures (140°C-240°C) using double layers of coating applied on C1S paper with theoretical coat weight of 5-6 gsm (grams per square meter). The emulsion showed better heat seal performance than Comparative Example 1, as shown in Table 9.
[0191] [Table 10]
[0192] Example 12: Synthesis of a polymer resin dispersion containing 35% fumaric acid modified rosin ester content using two monomer feeds Deionized water (18 grams), Disponil AFX 1080 (2.55 grams, 80% solids) and fumaric acid modified rosin ester dispersion (Filtrez 5014A, 545 grams, 28.2% solids) were added to a reaction vessel equipped with a condenser, thermometer, nitrogen inlet and overhead stirrer and heated to 70° C. under a nitrogen flow. Isoascorbic acid (2.45 grams), ammonium hydroxide (1.12 grams, 29%) and deionized water (23.01 grams) were added and held with stirring for 3 minutes. Copper sulfate (0.03 grams) and deionized water (2.85 grams) were added and held with stirring for 3 minutes. The first monomer mixture (methyl methacrylate MMA, 35.3 grams; n-butyl acrylate BA, 64.89 grams; acrylic acid, 1.86 grams; Aerosol OT75, 2.29 grams, (75% solids); and 2-ethylhexyl acrylate 2-EHA, 40.88 grams) was added over 50 minutes. The second monomer mixture (methyl methacrylate MMA, 89.3 grams; n-butyl acrylate BA, 37.45 grams; acrylic acid, 1.86 grams; Aerosol OT75, 2.29 grams, (75% solids); and 2-ethylhexyl acrylate 2-EHA, 14.3 grams) was then added over 50 minutes, followed by a 4.5 gram deionized water flush. The initiator feed (tertiary-butyl hydroperoxide, 3.61 grams, 70 wt %, in 46.93 grams of deionized water) was started simultaneously with the monomer feed and continued for 100 minutes, followed by a 30 minute hold with stirring during post-polymerization. Two separate solutions (sodium erythorbate, 19.27 grams, 12% solids in 1.5 grams of deionized water) and (tertiary-butyl hydroperoxide, 2.97 grams, 70 wt %, in 17.83 grams of deionized water) were added simultaneously over 30 minutes, followed by a 30 minute hold. The reaction was cooled to 30° C. and filtered. The desired aqueous polymeric resin dispersion containing 35% fumaric acid modified rosin ester content was obtained with the following properties: solids=45.7 wt%; Tg=5C; pH=8.13; particle size (volume average diameter, dv)=159 nm; Mn=23.85 kDa, Mw=135.26 kDa, PDI=5.67; viscosity=58.50 cPs.
[0193] Comparative Example 1: Synthesis of Acrylic Emulsion Polymer Containing Partially Neutralized Acid-Functional Support Resin The acid functional polymer described below was prepared by a high temperature continuous polymerization process as described in U.S. Patents 5,461,60, 4,414,370 and 4,529,787, all of which are incorporated herein by reference. The polymer was made using a continuous free radical polymerization process at relatively high temperatures in a homogeneous environment. The high reaction temperature produces low molecular weight polymers without the use of chain transfer agents. After the polymerization step, the resin was passed through a devolatilizer to remove unreacted monomers and process solvents. Using the above procedure, a polymer (acid functional polymer resin) was prepared by mixing 30% by weight of α-methylstyrene, 33% by weight of styrene, 6% by weight of 2-ethylhexyl acrylate, and 31% by weight of acrylic acid with the following properties: T g = 141°C; acid number = 227 mg KOH / gram; Mn = 3.4 kDa; PDI = 2.88; and Mw = 9.75 kDa.
[0194] The above acid functional polymer was dispersed in water by neutralizing a fraction of the acid groups with base under stirring and heating. For example, an aqueous polymer resin dispersion at 28.5 wt% solids was prepared by adding 220 grams of the polymer resin synthesized above to 473.7 grams of deionized water and 50.3 grams of ammonia (29 wt% active) in a reaction vessel equipped with a condenser and an overhead stirrer. The mixture was heated to 88°C-92°C under stirring and held for 4 hours, then cooled to room temperature and filtered to obtain a polymer dispersion with the following properties: polymer solids=28.5 wt%; pH=8.0; viscosity=200 cPs; and particle size (volume average diameter, dv)=<10 nm.
[0195] Following the synthesis of the partially neutralized acid-functional support resin above, the synthesis of a controlled rheology acrylic emulsion polymer was completed. Deionized water (31.1 grams) and the above polymer resin support dispersion (93.4 grams, 28.5% solids) were added to a reaction vessel equipped with a condenser, thermometer, nitrogen inlet, and overhead stirrer and heated to 82° C. under a nitrogen stream. Ammonium persulfate (0.66 grams) and deionized water (51.2 grams) were added and held with stirring for 3 minutes. A monomer mixture (methyl methacrylate, 17 grams; butyl acrylate, 38.8 grams; and 2-ethylhexyl acrylate, 24.9 grams) was added over 90 minutes, followed by a flush with 1.3 grams of deionized water and held for 30 minutes. tert-Butyl hydroperoxide (0.4 grams) and deionized water (2.38 grams) were added and held for 10 minutes. Sodium erythorbate (1.4 grams) and deionized water (3.2 grams) were added over 15 minutes and held for 10 minutes. The reaction was cooled to ambient temperature and filtered. The desired polymer resin emulsion was obtained with the following properties: viscosity at 25°C is 1150 cps measured with a Brookfield LV, spindle #3 at 30 rpm for 30 seconds; solids is 48 wt%; Tg=-27C; MFFT=<5C; acid number=64 mgKOH / gram; particle size (volume average diameter, dv)=81 nm; and Mw=826 kDa.
[0196] Comparative Example 2: Synthesis of a polymer resin dispersion containing 25% fumaric acid modified rosin ester content using one monomer feed A reaction vessel equipped with a condenser, thermometer, nitrogen inlet, and overhead stirrer was charged with deionized water (319 grams), Disponil AFX1080 (2.5 grams, 80% solids), and fumaric acid modified rosin ester dispersion (Filtrez 531, 313.8 grams, 28.3% solids) and heated to 85°C under nitrogen flow. The first initiator (ammonium persulfate APS 100% (1.35 grams) and deionized water (12.15 grams)) was added and held for 3-5 minutes. The monomer mixture (methyl methacrylate MMA, 125.21 grams; n-butyl acrylate BA, 79.5 grams; Aerosol OT75, 4.38 grams (75% solids); and 2-ethylhexyl acrylate 2-EHA, 58.13 grams) was added over 120 minutes, followed by a 15 gram deionized water flush. The initiator feed (ammonium persulfate APS 100% (1.35 grams) and deionized water (12.15 grams)) was started 60 minutes after the monomer feed and continued with stirring for 60 minutes. At the end of the APS and monomer feeds, the reaction mixture was held with stirring for 30 minutes during post polymerization. Two separate solutions: sodium erythorbate, 19.27 grams, 12% solids; tert-butyl hydroperoxide (2.97 grams, 70 wt%) dissolved in 1.9 grams of deionized water and added simultaneously over 30 minutes, followed by a 30 minute hold. The reaction was cooled to 30° C. and filtered. The desired polymer resin dispersion containing 25% fumaric acid modified rosin ester content is obtained with the following properties: solids=34.6 wt%; Tg=-26C; pH=8.3; particle size (volume average diameter, dv)=1851 nm; Mn=40.62 kDa, Mw=119.80 kDa; PDI=2.95; viscosity=16 cps.
Claims
1. 1. A method for producing a polymer emulsion, comprising: i) providing a resin dispersion comprising at least one resin in an aqueous solution; ii) adding a polymerization mixture comprising at least one polymer seed and at least one copolymerizable monomer to the resin dispersion; iii) preparing a polymer emulsion in water by radical emulsion polymerization of the polymerization mixture, the resin dispersion and the polymer seeds; A method comprising:
2. The method of claim 1 , wherein the at least one resin is derived from a bio-renewable source.
3. The method of claim 1 or claim 2, wherein the at least one resin comprises a rosin ester.
4. The method of claim 1 , wherein the at least one resin comprises a fumaric acid ester.
5. 5. The method of any one of claims 1 to 4, wherein the at least one resin has an acid value of from 125 mg KOH / g to 200 mg KOH / g.
6. 6. The method according to any one of claims 1 to 5, wherein the at least one resin has a number average molecular weight (Mn) from 600 g / mol to 800 g / mol and a weight average molecular weight (Mw) from 1500 g / mol to 15,000 g / mol.
7. 10. The method of claim 1 , wherein the emulsion polymerization monomers are added as two separate feeds, Feed 1 and Feed 2.
8. T of the supply 1 g is from -25°C to -15°C as measured by ASTM D3418-15.
9. T of the supply 2 g is from 20°C to 40°C as measured by ASTM D3418-15.
10. 2. The method of claim 1, wherein the copolymerizable monomer is selected from the group consisting of methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, i-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (meth)acrylic acid, itaconic acid, and combinations thereof.
11. The method of claim 1 further comprising an initiator.
12. The method of claim 11 , wherein the initiator is a redox initiator.
13. 13. The method of claim 11 or claim 12, wherein the initiator is selected from the group consisting of isoascorbic acid (IAA), t-butyl hydroperoxide (TBHP), and combinations thereof.
14. The method of claim 1 further comprising a catalyst.
15. The catalyst is copper(II) sulfate (CuSO 4 15. The method of claim 14, comprising:
16. 16. The polymer emulsion of any one of claims 1 to 15, wherein the polymer emulsion is substantially free of styrene.
17. 16. An aqueous composition comprising a polymer emulsion according to any one of claims 1 to 15.
18. An aqueous composition according to claim 17; A substrate; Including, a coating.
19. 20. The coating of claim 18, wherein the substrate is selected from the group consisting of paper, paperboard, and cardboard.